Co-creative research for transitioning toward a fair and sustainable agri-food system in Brussels, Belgium - Hermesse, Julie; Vankeerberghen, Audrey; Lohest, François; Truyffaut, Alice (Frontiers in Sustainable Food Systems, 2023)
After decades of urbanization and agricultural industrialization, the relationships between cities and their agri-food systems have been profoundly transformed, especially in developed countries. To make agri-food systems more sustainable the pressing need to rethink food-related practices in cities has received momentum in the past 20 years across many European cities. Transdisciplinary and participatory research can generate knowledge and promising solutions to facilitate the transition of urban agri-food systems. This article highlights the contributions of six research projects driven by the notion of “co-creation” research for urban agri-food system transition, using Brussels as the research context (program “Co-Create”). The article outlines the main research foci and characteristics of the six “Co-Create” projects funded by this call, how they are embedded in the broader dynamics and initiatives of Brussels, and the theoretical foundations of the notion of “co-creation” research that sits at the intersection of transdisciplinary and participatory action research. Subsequently the paper illustrates how the six Co-Create project brought together different actors in Brussels including researchers, citizens, associations, and government agencies, that were united with a shared awareness of the need for change of the city's agri-food system. The six research consortia targeted different issues across three aspects of the agri-food system: agricultural production in urban areas, food distribution and marketing, and accessibility and democratization of sustainable food. We critically reflect on some common insights generated by the six projects, and particularly (a) a series of recommendations that were drafted for public authorities and called for the acceleration and strengthening of efforts for urgent changes in the agri-food system of Brussels, and (b) findings that address the epistemological and methodological strengths and limitations of conducting co-creative research processes to facilitate agri-food system transition. We also discuss how the Co-Create projects might have created a historical momentum that has encouraged the placing of the transition of agri-food systems on the political agenda of Brussels, and by identifying future challenges for agri-food system transitions in Belgium.